Genomic prediction in upland rice for aluminum tolerance in Latin America - Grenier, Cecile; Bartholomé, Jerome Brice; Frouin, Julien (2024)
This data set contains a phenotypic information collected on a population of 334 S0:4 families extracted from synthetic population managed through recurrent selection and phenotyped in Colombia in 2020. The traits were recorded in two soil conditions (ALU: the naturally aluminum toxic soil condition, and LIM: after liming to correct the toxicity). The genotypic data was obtained on 334 S0 plants by GBS (Mse1 and Pst1) after imputation and ended in a set of 9928 SNPs. (2023-11-08)